RISK FACTORS FOR NODAT UNDER IMMUNOSSUPPRESSANTS IN RENAL TRANSPLANTED CHILDREN. Issue 1 (14th December 2015) - Lancia, Pauline; Zhao, Wei; Maisin, Anne; Simon, Dominique; Elie, Veronique; Elie, Valery; Jacqz-Aigrain, Evelyne
Abstract : Introduction: New Onset Diabetes After Transplantation (NODAT) is a major complication of immunossuppressive therapy and an risk factor for transplant rejection. Its incidence ranges from 4 to 25% in adults. In 2013, L. Elens and coworkers reported the association of two genetic variants PPARα rs4253728 and POR*28 rs1057868 with the occurrence of NODAT in renal transplanted adults treated with tacrolimus, MMF and corticosteroïds. Objective: Our objective was to assess the impact of these two genetics variants along with additional risk factors (age, sex, HLA missmatches…) on the occurrence of NODAT among renal transplanted children treated with tacrolimus, MMF, and corticoids. Materiel and method: Genotypes were determined using allelic discrimination technique. The univariate and mulivariate analyses have been performed using SPSS v15. Results: 238 renal transplanted children were identified between 1990 and 2013, 109 were treated with tacrolimus and included in the study (63 boys/46 girls). The mean age at time of transplantation was 10.8 years (±0.5) and mean duration of floow-up was 4 years (±0.3). A significant association of NODAT was evidenced with POR*28 (p=0.010) but not with PPARα (p=0.434), number of HLA mismatches (p=0.004) and donor's CMV serology (p=0.026). Conclusion: This pilot study validated the association between the SNP POR*28 and the occurrence of NODAT in renal transplanted children treated with tacrolimus. Early identification of patients carrying POR*28 genetic variant might allow to anticipate the risk of NODAT and improve patient's care.